Voting behavior in Asian democracies: A comprehensive synthesis of contemporary research - Sulaiman, Suryanagara Muhammad Iftitah; Rahmatunnisa, Mudiyati; Bainus, Arry; Umam, Ahmad Khoirul (Masyarakat, Kebudayaan dan Politik, 2025)
This article aims to systematically review the literature on voting behavior in Asian democracies, particularly in the post-Cold War era, to consolidate fragmented insights and to gain a strong understanding about existing scholarships and political development after the third wave of democratization in the region. Around 41 noteworthy publications from the Scopus database, published from 1990 to 2023, were analyzed by highlighting the diversity and limitations of conceptualizations, theoretical lens, and also methodological approaches to understand complexities and irregularities especially in the factors that influence voting behavior in Asian democracies. This study finds that voting behaviors in Asian democracies are shaped by a complex interplay of sociological, psychological, and rational, as well as institutional and structural factors. As political landscapes change, innovative electoral trends keep arise, and the region is politically and culturally heterogeneous, and maintaining an accurate and contextually based approach to reviewing voter behavior in Asia will remain fundamental for developing both academic discourse and also sensible democratic governance in the region.